2020
DOI: 10.3390/ijerph17092992
|View full text |Cite
|
Sign up to set email alerts
|

Patient Reported Outcome Measures of Sleep Quality in Fibromyalgia: A COSMIN Systematic Review

Abstract: Poor sleep quality is a common concern and a troublesome symptom among patients suffering from fibromyalgia. The purpose of this review was to identify and describe the available patient reported outcome measures (PROMs) of sleep quality validated in adult people diagnosed with fibromyalgia. The COSMIN and PRISMA recommendations were followed. An electronic systematized search in the electronic databases PubMed, Scopus, CINAHL Plus, PsycINFO, and ISI Web of Science was carried out. Validation studies of PROMs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…The total score of the survey is obtained from the sum of the 7-item scores. The scores range from 0 to 21, and lower scores indicate better sleep quality [ 15 ].…”
Section: Materials-methodsmentioning
confidence: 99%
“…The total score of the survey is obtained from the sum of the 7-item scores. The scores range from 0 to 21, and lower scores indicate better sleep quality [ 15 ].…”
Section: Materials-methodsmentioning
confidence: 99%
“…Sleep disorders are among the most prevalent complaints in primary medical care and in the general population [4][5][6][7][8][9][10][11][12]. Epidemiological data indicate that insomnia is the most frequent sleep complaint [3].…”
Section: The Sleep-disorder Scalesmentioning
confidence: 99%
“…For example, the presence of sleep complaints has been reported even when SOL, Wakefulness After Sleep Onset (WASO), TST and awakening were similar to those reported in normal non-complaining individuals [2]. Complaints of disturbed (or poor quality) sleep have been confirmed in almost every country [3] and among patients in all specialties of medicine [4][5][6][7][8][9][10][11][12]. Untreated sleep disorders may lead to potentially life-threatening symptoms, considering that sleep disorders are not only a consequence of medical illness but are also primary drivers of other illnesses [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is likely that the COSMIN group did not have any direct influence on the quality of the review. Climent-Sanz et al 4 reviewed instruments designed to assess sleep problems. Five instruments were identified that were suitable for review, although these were only covered by seven publications.…”
Section: Descriptions Of the Four Ratings Followmentioning
confidence: 99%